The effects of acute alcohol consumption on recovery from a simulated rugby match - Barnes, M. J.; Mundel, T.; Stannard, S. R. (Journal of Sports Sciences, 2012)
In this study, we investigated the effects of acute post-exercise alcohol consumption on measures of physical performance, creatine kinase, and immunoendocrine function in the 48 h following a rugby game simulation. Ten male senior rugby union players completed a rugby game simulation after which they consumed either 1 g of alcohol per kilogram of body mass or a non-alcoholic control beverage. Agility, 15 m sprint, countermovement jump, and srummaging performance were assessed pre-simulation and 24 and 48 h post-simulation. White blood cell count, testosterone, cortisol, and creatine kinase were measured before the simulation and 30 min, 12, 24, 36, and 48 h after the simulation. One week after the first trial, participants completed the second simulation after which the other beverage was consumed. The acute consumption of alcohol after a rugby game simulation negatively affected countermovement jump performance in the days following the simulation (P = 0.028). No differences between treatments were observed for the other criterion measures made in this study. In conclusion, after 80 min of a simulated rugby game, the consumption of 1 g of alcohol per kg body mass negatively impacts lower body vertical power output. However, performance of tasks requiring repeated maximal muscular effort is not affected.